A propensity score analysis of over 12, 000 pancreaticojejunal anastomoses after pancreaticoduodenectomy: does technique impact the clinically relevant fistula rate?. Issue 10 (October 2020) - Kone, Lyonell B.; Maker, Vijay K.; Banulescu, Mihaela; Maker, Ajay V.
Abstract: Background: Clinically relevant postoperative pancreatic fistula (CR-POPF) remains a major cause of morbidity in patients undergoing pancreatic surgery. Controversy exists as to whether there is any difference in CR-POPF with a Duct-to-Mucosa (DTM) versus an Invagination (IG) pancreaticojejunostomy (PJ). Methods: Demographic, perioperative, intraoperative, and postoperative data were captured from the American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) 2014–2017 databases. Potential confounders were included in a logistic regression and a propensity score model. The primary outcome was CR-POPF. Results: A total of 12, 361 pancreaticojejunal anastomoses were performed with 11, 168 patients undergoing DTM (90%) and 1193 undergoing IG (10%) after pancreaticoduodenectomy. Amongst all patients, there was no significant difference in CR-POPF between DTM and IG on multivariate (OR = 0.95, p = 0.64) or propensity score analysis (OR = 0.99, p = 0.93). After stratification by pancreatic gland texture and duct size, there was a decrease in CR-POPF with DTM amongst patients with duct size greater than 6 mm on multivariate analysis (OR = 0.35, p = 0.009) and propensity score analysis (OR = 0.40, p = 0.018). There were no significant differences in any other strata. Conclusion: DTM or IG technique are not associated with CR-POPF for patients with average size pancreatic ducts; however, DTM is preferable in patients with large pancreatic duct diameter (>6 mm).